Accounting Information System Development End-user-based for Improving Digital Business - Jaluanto Sunu Punjul Tyoso; Siti Aminah; Hastin Andriyani (International Journal of Economics and Management Research, 2022)
This study aimed to determine the end user's role in system strategy, conceptual design and system selection for the successful development of accounting information systems at PT. Radik Jaya, Indonesia and to know the supporting factors and constraints for the development of accounting information systems in PT. Radik Jaya Indonesia. The research method used was qualitative with a case study approach. Data was collected with observation and in-depth interviews directly with key sources of information (CFO, Financial staff, HR and general staff), documentation, credibility, and source triangulation. Taxonomy was used as the data analysis method. The result showed that the roles of the user to determine the success of the development of accounting information system at PT. Radik Jaya Indonesia. These roles include the user's role in system strategy, conceptual design, and system selection. The role of users in the system strategy was to provide information and proposals related to the features carried out the development of accounting information systems in order to run effectively. The role of the user in conceptual design was to ensure the design of the accounting information system in accordance with the PSAK and in accordance with the description of the information provided in the process of designing the system strategy. The selection of the system was done in detail, the user plays a role in the selection of the system by paying attention to the features that have been applied in accordance with the operational needs of the company's work and business. The information presented displayed well. The client guarantees the costs caused by the organization during the time spent fostering the bookkeeping data framework as per the plan that has been made.